GSTP1 and CYP2B6 Genetic Polymorphisms and the Risk of Bronchopulmonary Dysplasia in Preterm Neonates - Zachaki, Sophia; Daraki, Aggeliki; Polycarpou, Elena; Stavropoulou, Chrysa; Manola, Kalliopi N.; Gavrili, Stavroula (American Journal of Perinatology, 2017)
Objectives Antioxidant response plays a key role in bronchopulmonary dysplasia (BPD) pathogenesis. The glutathione-S-tranferases pi 1 (GSTP1) and cytochrome P450 (CYP) detoxification enzymes protect cells from oxidative damage. The aim of the study was to investigate whether the A313G GSTP1 and G516T CYP2B6 inactivating polymorphisms could be associated with BPD susceptibility.Study Design To test this hypothesis, we conducted a case–control study enrolled 138 premature neonates ≤32 weeks of gestational age; of the 138, 46 developed BPD and 92 did not develop BPD. Genomic deoxyribonucleic acid was extracted from neonates' peripheral blood and was used as template for GSTP1 and CYP2B6 genotyping using the real-time polymerase chain reaction method.Results Our report provides evidence for a possible pathogenetic role of the G516T CYP2B6 polymorphism in BPD susceptibility. Although no differences in the frequencies of the GSTP1 variant genotypes were noticed between premature neonates who developed BPD and neonates who did not develop BPD, a significantly higher frequency of the GSTP1 polymorphism was observed in extremely low birth weight infants. Despite the small sample size, it is very interesting the fact that all neonates ≤1,000 g carrying the homozygous mutant GSTP1 genotype developed BPD.Conclusion Our results underscore the significance of both CYP2B6 and GSTP1 polymorphisms in modulating the risk of BPD.
Keywords: glutathione-S-tranferases pi 1; cytochrome P450; single nucleotide polymorphism; oxidative stress